An Analysis of Journey Mapping to Create a Palliative Care Pathway in a Canadian First Nations Community: Implications for Service Integration and Policy Development. (20th July 2017) - Koski, Jessica; Kelley, Mary Lou; Nadin, Shevaun; Crow, Maxine; Prince, Holly; Wiersma, Elaine C; Mushquash, Christopher J
Providing palliative care in Indigenous communities is of growing international interest. This study describes and analyzes a unique journey mapping process undertaken in a First Nations community in rural Canada. The goal of this participatory action research was to improve quality and access to palliative care at home by better integrating First Nations' health services and urban non-Indigenous health services. Four journey mapping workshops were conducted to create a care pathway which was implemented with 6 clients. Workshop data were analyzed for learnings and promising practices. A follow-up focus group, workshop, and health care provider surveys identified the perceived benefits as improved service integration, improved palliative care, relationship building, communication, and partnerships. It is concluded that journey mapping improves service integration and is a promising practice for other First Nations communities. The implications for creating new policy to support developing culturally appropriate palliative care programs and cross-jurisdictional integration between the federal and provincial health services are discussed. Future research is required using an Indigenous paradigm.